Perancangan Antarmuka Sistem Informasi Simpan Pinjam Pada BUMDES Karangtengah Gemilang Dengan Menggunakan Metode Human Centered Design (HCD) - Amanda Puti Wibawa; Satrio Hadi Wijoyo; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
BUMDES Karangtengah Gemilang has a Savings and Loans Unit which is used by Karangtengah Village residents to loan and save money. In facilitating lending activities, BUMDES Karangtengah Gemilang has entered into a contract with an IT team appointed by the village to create a savings and loan information system. But in developing information, the IT team did not take the right approach to a design display system that was suitable for the needs and circumstances of the objects that the system would implement. With this problem, the Chairman of BUMDES and the management are afraid that the appearance of the system design is not appropriate. Therefore, before developing the system required interface design using an approach tailored to the needs and circumstances of the Karangtengah Gemilang BUMDES. From the interview results, it is known that the Human Centered Design (HCD) approach is suitable for designing a savings and loan information system interface. Research is carried out by planning a human-centered design process, understanding and specifying the context of use, specifying user needs, producing design solutions, and design evaluation. The resulting design solution is a prototype that the user can try for evaluation with focus group discussions, to find out whether the design of the design solution is in accordance with the user's wants and needs. The result of FGD was 15 repair agreements that it had to re-iterate the HCD stage.